2022
DOI: 10.1109/jphot.2022.3203424
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Conventional and Imaging MIMO OWC Systems Using Linear Array Design

Abstract: Multiple-input-multiple-output (MIMO) optical wireless communication systems are potential candidates for high-speed data transmission in indoor environments. In this work, we present an experimental evaluation of two different MIMO systems, i.e., conventional-MIMO (c-MIMO) and imaging-MIMO (i-MIMO) in terms of design considerations. Both systems use the same transmitter configuration featuring a one-dimensional (light-emitting diode) LED transmitting array. On the receiver side, the c-MIMO system employs a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…The system improves the frequency spectrum utilization and the throughput of the system by means of the spatial multiplexing, which can solve the problem of original low bandwidth of commercial high-power LED array light sources under SISO scheme. Previous studies have shown that the imaging MIMO-UWOC has lower spatial correlation than the non-imaging MIMO-UWOC, so that it can achieve higher multiplexing gain [26] .…”
Section: Resultsmentioning
confidence: 99%
“…The system improves the frequency spectrum utilization and the throughput of the system by means of the spatial multiplexing, which can solve the problem of original low bandwidth of commercial high-power LED array light sources under SISO scheme. Previous studies have shown that the imaging MIMO-UWOC has lower spatial correlation than the non-imaging MIMO-UWOC, so that it can achieve higher multiplexing gain [26] .…”
Section: Resultsmentioning
confidence: 99%